Librational Dynamics of Spin-Labeled Membranes at Cryogenic Temperatures From Echo-Detected ED-EPR Spectra - Bartucci, Rosa; Aloi, Erika (Frontiers in Molecular Biosciences, 2022)
Methods of electron spin echo of pulse electron paramagnetic resonance (EPR) spectroscopy are increasingly employed to investigate biophysical properties of nitroxide-labeled biosystems at cryogenic temperatures. Two-pulse echo detected ED-spectra have proven to be valuable tools to describe the librational dynamics in the low-temperature phases of both lipids and proteins in membranes. The motional parameter, 〈α^2 〉 τ_c, given by the product of the mean-square angular amplitude, 〈α^2 〉, and the rotational correlation time, τ_c, of the motion, is readily determined from the nitroxide ED-spectra as well as from the W-relaxation rate curves. An independent evaluation of 〈α^2 〉 is obtained from the motionally averaged 14N-hyperfine splitting separation in the continuous wave cw-EPR spectra. Finally, the rotational correlation time τ_c can be estimated by combining ED- and cw-EPR data. In this mini-review, results on the librational dynamics in model and natural membranes are illustrated.